Introduction to the Plasma State of Matter - Adhikari, B. R.; Khanal, R. (Himalayan Physics, 2013)
Plasma is a quasineutral gas of charge and neutral particles which exhibits collective behavior. Because of its distinct behavior it is often termed as the fourth state of matter. It is of interest as it has found applications in diverse areas such as, controlled thermonuclear fusion, gas lasers, lightning, medicine, space science, electronics, etc. In this article we present an introduction to the plasma state of matter and discuss some of its applications. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 60-64 Uploaded date: 12/23/2013